Effects of bootstrap current on magnetic configuration in Chinese first quasi-axisymmetric stellarator - Haifeng Liu; Jian Zhang; Yuhong Xu; Akihiro Shimizu; Wilfred Anthony Cooper; Shoichi Okamura; Mitsutaka Isobe; Xianqu Wang; Jie Huang; Jun Cheng; Hai Liu; Xin Zhang; et al. (Nuclear Fusion, 2023)
Neoclassical properties in quasi-axisymmetric (QA) stellarators are analogous to these in tokamaks. Consequently, a substantial bootstrap current could significantly modify the MHD equilibrium properties of a QA stellarator, which is an important characteristic in this type of stellarator. This paper is dedicated to systemically investigate the effects of bootstrap current on the magnetic configuration in Chinese first quasi-axisymmetric stellarator (CFQS). For the first time, self-consistent bootstrap currents in free-boundary equilibria are calculated with an accurate Fokker–Planck neoclassical numerical mode in CFQS. Several important results are achieved: (a) as the bootstrap current grows with increasing volume-averaged normalized pressure $β $ , magnetic shear develops in the bulk plasma and meanwhile, a deep magnetic well is robustly sustained, which leads to improved stabilization of interchange modes up to $β \sim 2.0{{% }}$ . (b) In the analysis of global ideal MHD instability, as the bootstrap current rises to 39 kA ( $β \sim 1.3{{% }}$ ), external kink modes become destabilized and the unstable mode with m / n = 2/1 is dominant. (c) From $β = 0$ to 1.5%, the bootstrap current hardly changes the QA property and a low neoclassical transport is maintained. However, as $β $ is enhanced beyond 2.0%, the substantial bootstrap current gives rise to an increase of non-QA magnetic field components, which weakens the neoclassical transport properties. (d) An increase of the negative magnetic shear at the core region by the bootstrap currents has a favorable effect on the properties of J (second adiabatic invariant). The maximum- J region can be extended by raising bootstrap currents.